1988
DOI: 10.1007/bf00215443
|View full text |Cite
|
Sign up to set email alerts
|

44-kDal bone phosphoprotein (osteopontin) antigenicity at ectopic sites in newborn rats: kidney and nervous tissues

Abstract: Previous immunohistochemical data have shown that the 44-kDal bone phosphoprotein (44K BPP, also called sialoprotein I or oestopontin) recently isolated in our laboratory was synthesized by osteoblasts and osteocytes and was expressed early during differentiation of bone-forming cells. We report here the presence of 44K BPP antigenicity at certain ectopic sites, namely, the proximal-convoluted tubule of the kidney, neurons, sensory and secretory cells in the internal ear. To insure specificity and reproducibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(46 citation statements)
references
References 32 publications
3
42
1
Order By: Relevance
“…24 cDNA cloning and sequencing have shown that this gene encodes osteopontin (2ar, sialoprotein I, 44-kD bone phosphoprotein, and secreted phosphoprotein I), a noncollagenous sialoprotein that was first isolated from mineral bone extracellular matrix 21222526 but that has also been immunodetected in other tissues and fluids (e.g., kidney, uterus, plasma, and milk). 27 " 29 By Northern blot analysis, osteopontin mRNA was previously strongly detected in bone and the kidney, 23 aorta, and carotid artery. 22 The high steady-state level of osteopontin mRNA found in the aorta demonstrated that aortic tissue in conjunction with bone or the kidney was a relative specific site of osteopontin expression.…”
Section: Discussionmentioning
confidence: 98%
“…24 cDNA cloning and sequencing have shown that this gene encodes osteopontin (2ar, sialoprotein I, 44-kD bone phosphoprotein, and secreted phosphoprotein I), a noncollagenous sialoprotein that was first isolated from mineral bone extracellular matrix 21222526 but that has also been immunodetected in other tissues and fluids (e.g., kidney, uterus, plasma, and milk). 27 " 29 By Northern blot analysis, osteopontin mRNA was previously strongly detected in bone and the kidney, 23 aorta, and carotid artery. 22 The high steady-state level of osteopontin mRNA found in the aorta demonstrated that aortic tissue in conjunction with bone or the kidney was a relative specific site of osteopontin expression.…”
Section: Discussionmentioning
confidence: 98%
“…The molecular effectors controlling differentiation in the osteoblastic lineage until the stage of a mineralizing cell have not been identified. Osteoblast differentiation is marked by the sequential activation of many genes encoding bone extracellular matrix proteins like alkaline phosphatase (3), collagens (49), proteoglycans (5), bone sialoprotein (16), osteopontin (30), and osteocalcin (39) and hormone receptors such as vitamin D 3 and parathormone receptors (40). Most of these genes are expressed in a differentiation-dependent manner in osteoblasts but also in other cell types.…”
mentioning
confidence: 99%
“…However, OPN is also pres-ent as a normal constituent of kidney, placenta, uterus, sensory, and neural cells of the inner ear, blood, and milk. Most importantly, it is secreted by many transformed and neoplastic cells (Craig et al, 1987;Yoon et al, 1987;Mark et al, 1988;Nomura et al, 1988;Senger et al, 1988Senger et al, , 1989Swanson et al, 1989). Because of its widespread occurrence, several other names have been coined: 44-kDa bone phosphoprotein (Butler, 1989), 2arl (Smith and Denhardt, 1987), and secreted phosphoprotein 1 (SPP-1) (Senger et al, 1988).…”
mentioning
confidence: 99%